Securing access to electricity with variable renewable energy in the Philippines: Learning from the Nordic model - Shinichi Taniguchi (Asian Development Bank Institute (ADBI), 2019)
Although access to electricity has improved in the Philippines, the country still faces an energy insecurity problem. The country is highly dependent on coal power and large-scale transmission lines to meet its growing demand for electricity; while aiming to supply electricity to the cities, rural areas have fallen behind. This approach has resulted in higher electricity rates, urban and rural inequality in electricity distribution, and a huge environmental impact, while the system reliability is at risk. Variable renewable energy (VRE) plays a key role in resolving this problem, because of its abundance and a recent trend for cost competitiveness. The Nordic model provides useful suggestions in integrating a high share of VRE, but it has a limitation in the interconnection of underdeveloped power grids with off-grid areas, like in the Philippines. Constructing an effective interconnector is difficult, because it is subject to the future installation of VRE. There is an alternative measure: the distributed VRE model. The Nordic model also provides useful suggestions, such as the requirement for flexible resources (e.g., hydroelectric and storage resources). This model is beneficial in improving the local electrification rate and the energy consumption rate (ECR) per capita, leading to economic growth. The last analysis indicates that the combination of VRE and storage would be more cost-competitive than the traditional fossil fuel generation model.
Keywords: C3; N55; Q21; Q28; Q41; Q42; Q54; R11; 330; VRE; Nordic model; interconnector; rural electrification; energy consumption rate; ECR; distributed model